Full-Scale Model Experimental Study of the Flexural Behavior of Hollow Slabs Strengthened by UHPC - Jinzhi Zhou; Zihao Wen; Weiqi Mao; Chuheng Zhong; Kangning Wang; Chenxu Zhou (Advances in Materials Science and Engineering)
The hollow slabs strengthened by ultrahigh performance concrete (UHPC) composite beam show many advantages over traditional reinforcement methods. In this paper, full-scale model load tests were carried out on an nonstrengthened prestressed concrete hollow slab and an UHPC-strengthened prestressed concrete hollow slab, comparing the load deflection, crack width, bearing capacity, deformation resistance, and self-vibration frequency of the two. Static loading experimental results indicate that UHPC enhances the overall performance of prestressed concrete hollow slabs by decreasing deflection and crack width and improving bearing capacity. The strengthening effects of UHPC on a prestressed concrete hollow slab’s flexural behavior are also discussed, such as deflection, crack width, bearing capacity, deformation resistance, self-vibration frequency, flexural behavior, and cracking load. Deflection and crack width under a load of 800 kN decreased by 45.8% and 56.3%, respectively, and the initial self-vibration frequency, ultimate bearing capacity, and cracking load increased 19.2%, 21.4%, and 50%, respectively. The plane assumption can be made generally throughout the overall test process while using UHPC strengthening, which significantly constrains crack width and improves stiffness and deformation capacity. The UHPC layer and the prestressed concrete hollow slab were connected by shear studs to produce a good composite action between them, and the bending performance and bearing capacity of the whole structure were clearly improved. In addition to experiments, a validated numerical model is developed to verify the flexural performance of hollow slab strengthened by UHPC.